2011
DOI: 10.1371/journal.pone.0025200
|View full text |Cite
|
Sign up to set email alerts
|

Barcoded Pyrosequencing Reveals That Consumption of Galactooligosaccharides Results in a Highly Specific Bifidogenic Response in Humans

Abstract: Prebiotics are selectively fermented ingredients that allow specific changes in the gastrointestinal microbiota that confer health benefits to the host. However, the effects of prebiotics on the human gut microbiota are incomplete as most studies have relied on methods that fail to cover the breadth of the bacterial community. The goal of this research was to use high throughput multiplex community sequencing of 16S rDNA tags to gain a community wide perspective of the impact of prebiotic galactooligosaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
226
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 283 publications
(257 citation statements)
references
References 51 publications
19
226
1
2
Order By: Relevance
“…3A). These findings confirm the highly specific bifidogenic response of GOS, which was previously demonstrated in humans (32).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…3A). These findings confirm the highly specific bifidogenic response of GOS, which was previously demonstrated in humans (32).…”
Section: Resultssupporting
confidence: 91%
“…In a previous study (25,32), we reported a significant and remarkably specific enrichment of Bifidobacterium populations in human subjects during dietary supplementation with GOS (as demonstrated by 454 sequencing, genus-specific qRT-PCR, and quantitative culture), which is in agreement with data from other GOS feeding studies (33)(34)(35)(36)(37)(38). Cultural enumeration of fecal samples during the human trial allowed us to identify individuals in which bifidobacteria were enriched by GOS and from whom strains likely to utilize GOS in vivo could be selected.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The best sources of naturally occurring prebiotics may be found in vegetables such as artichokes, onions, chicory, garlic and leeks (167) . There are numerous studies in which the bifidogenic properties of prebiotics are shown (121,122,166,(168)(169)(170)(171) . In addition, increase in abundance of lactobacilli (121,122) and F. prausnitzii (170,172) has been shown.…”
Section: Prebioticsmentioning
confidence: 99%